Antidumping Law. The Anatomy of a Privilege: A anatomia de um privilégio - de Saules Nogueira, Jorge Henrique; Salzer Procópio, Thais (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2023)
This article analyzes the international and domestic regulation of anti-dumping law and presents its consequences based on the Austrian Theory of Economic Intervention. Dumping occurs when companies from one country offer goods and products to other countries at prices lower than those charged in their own domestic markets. The concept of dumping has been distorted to accommodate the interests of the national industry. The application of anti-dumping measures by the Brazilian state implies the reduction of the exposure of the national industry to international competition and, consequently, the encumbrance of products and goods purchased by domestic consumers and by the industry located downstream of the production chains. The analysis of practical cases of anti-dumping measures implemented in Brazil - such as those applied to garlic, Chinese shoes and adipic acid - shows that, in addition to distorting the market, they make products more expensive and prevent more Brazilians from having access to these products.